Pemberian kredit dilihat dari dana pihak ketiga dan kinerja keuangan pada perusahaan Perbankan - Muhammad Rivandi; Aminar Sutra Dewi; Febsri Susanti; Dewi Zulvia (Politeknik Ganesha Medan, 2023)
Loans are loans or bills agreed between parties. This study aims to determine the effect of third party funds and financial performance on gifts to banking companies on the Indonesia Stock Exchange. Source of data used in this study is secondary data in the formof annual reports. The population used in this study are all banking companies listed on the Indonesia Stock Exchange (IDX) in the 2017 -2021 period that were selected using purposive sampling techniques. The number of samples used in the study were 11 companies. The analytical method used is multiple regression analysis. Based on the test results it was found that Third Party Funds (DPK) had a positive and significant effect on lending to banking companies on the Indonesia Stock Exchange, while the Capital Adequacy Ratio (CAR) and Non Performing Laon (NPL) had no effect on lending to banking companies in Indonesia stock exchange.